Design and Implementation of D08-32 Tamper Laser Motor Controller - ZHANG Baoming (机车电传动)
In D08-32 tamper network control system, laser collimation system is used to improve the precision of linear tamper operation, and motor control is the key technology. In order to further improve the accuracy of laser collimation system, and improve the working efficiency, a laser power controller based on DSP was designed to realize laser motor PID overshoot control and overcurrent protection function. The general structure, software and hardware design of laser motor controller was introduced in detail. The verification and application showes that the controller has perfect function and good performance, which can reduce the application failure rate, and improve the stability and reliability of laser collimation system